2018
DOI: 10.1111/jcmm.13526
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide enhances TGF‐β1 signalling pathway and rat pancreatic fibrosis

Abstract: Pancreatic stellate cells (PSCs) play a critical role in fibrogenesis during alcoholic chronic pancreatitis (ACP). Transforming growth factor‐beta1 (TGF‐β1) is a key regulator of extracellular matrix production and PSC activation. Endotoxin lipopolysaccharide (LPS) has been recognized as a trigger factor in the pathogenesis of ACP. This study aimed to investigate the mechanisms by which LPS modulates TGF‐β1 signalling and pancreatic fibrosis. Sprague‐Dawley rats fed with a Lieber‐DeCarli alcohol (ALC) liquid d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 36 publications
1
19
0
1
Order By: Relevance
“…TGF-β is one of the strongest fibrogenic cytokines, and it is involved in the fibrogenesis of many diseases ( Meng et al, 2016 ; Kim et al, 2018 ; Ma and Meng, 2019 ). During CP progression, upregulation of TGF-β in the pancreas further activates PSCs, promotes the synthesis of the ECM, and accelerates pancreatic fibrosis ( Liu P. et al, 2019 ; Sun et al, 2018 ; Xu et al, 2018 ). To explore the detailed mechanism of baicalin inhibiting PSC activation, we further isolated the primary PSCs of mice, cultured them to the second generation, and stimulated them with TGF-β1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGF-β is one of the strongest fibrogenic cytokines, and it is involved in the fibrogenesis of many diseases ( Meng et al, 2016 ; Kim et al, 2018 ; Ma and Meng, 2019 ). During CP progression, upregulation of TGF-β in the pancreas further activates PSCs, promotes the synthesis of the ECM, and accelerates pancreatic fibrosis ( Liu P. et al, 2019 ; Sun et al, 2018 ; Xu et al, 2018 ). To explore the detailed mechanism of baicalin inhibiting PSC activation, we further isolated the primary PSCs of mice, cultured them to the second generation, and stimulated them with TGF-β1.…”
Section: Discussionmentioning
confidence: 99%
“…Many experiments have demonstrated that the activation of pancreatic stellate cells (PSCs) and subsequent production of extracellular matrix (ECM) play critical roles in the progression of pancreatic fibrosis in CP ( Bynigeri et al, 2017 ; Li et al, 2018 ). PSCs remains quiescent under physiological conditions, but they are activated once the pancreas is exposed to various damage factors, especially the inflammatory factors released by the local infiltrated inflammatory cells in the microenvironment of the pancreas ( Sun et al, 2018 ; Xue et al, 2018 ). However, whether baicalin interferes with the activation of PSCs, as well as its detailed molecular mechanism, remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In this work we discovered that in cancer cells expressing TLR4, HMGB1 can induce TGF-b production and secretion (Figure 1). Interestingly, TLR4 has recently been shown to mediate TGF-b production when activated by lipopolysaccharide (LPS), its pathogen-associated ligand, and some endogenous stimuli such as hyaluronic acid (25,26). It was also demonstrated that HMGB1-induced activation of TGF-b production in TLR4expressing cells takes place through the activator protein 1 (AP-1) transcription factor and its upstream pathway (9).…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1 is a member of TGF-beta superfamily, which plays a role in several biological processes [19]. It has been uncovered that TGF-β1 is a key regulator of PSC activation and ECM production [20]. A previous study revealed that TGF-β1 overexpression induced CP in murine pancreas [21].…”
Section: Discussionmentioning
confidence: 99%